Transformation of Terraces with Irrigation Systems: Profitability and Water Savings in Potato Crop (Solanum tuberosum L.) - Poma Chamana, Russell; Flores Marquez, Ricardo; Cordova Tadeo, Joel; Quello Huamaní, Antony Arturo; Arapa Quispe, José; Solórzano Acosta, Richard Andi (MDPI, 2025)
MDPI stays neutral with regard to jurisdictional claims in published maps and institutional affiliations.